(untitled) (Nepal Journal of Health Sciences, 2021)
Gestational diabetes mellitus (GDM) can be defined as any degree of glucose intolerance with onset or first recognition during pregnancy. Screening for GDM is done usually at 24-28 weeks of gestation. In this case a 27-year-old primigravida who was diagnosed as GDM after a one step approach at 22 weeks of pregnancy. Institution of management early by the help of one step diagnosis was associated with successful outcome. The case highlights the importance of diagnosing GDM early especially in developing countries where resources are limited.